Biological and ecological factors contributing to the successful use of entomopathogenic nematodes (Rhabditida: Steinernematidae and Heterorhabditidae) for the control of codling moth, Cydia pomonella (L.) (Lepidoptera: Tortricidae) under South African conditions - De Waal, Jeanne Yvonne (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.